Noise level analysis to reduce noise exposure at PT. IT. Issue 1 (1st January 2019) - Suhardi, Bambang; Abdu Haq Navi, Muhammad; Dwi Astuti, Rahmaniyah
Abstract: PT. IT is a textile company that produces grey cloth and printing batik. The production process of making grey cloth and printing batik uses a machine that has the potential to cause noise. The noise level that occurs in one production area reaches 100 dB. This value exceeds the threshold value required by the Republic of Indonesia Minister of Health Regulation No 70 of 2016. Therefore, it is necessary to do research to reduce noise levels in the production area. The noise level measurement and calculation procedure refer to SNI 7231-2009 and KEP-48/MENLH/11/1996. The calculation of the maximum time of exposure to noise workers refers to NIOSH. Noise impact questionnaires are processed with descriptive statistics. The calculation of Noise Reduction Rating (NRR) refers to the Regulation of the Minister of Health of the Republic of Indonesia No 70 in 2016. From the 16 measurement points in the weaving department, 11 points with noise levels above NAB are obtained. The impact of noise perceived by workers includes communication disruption, physiological disorders, and psychological disorders. In order to overcome these problems, it was proposed noise control by using Ear Protector in the form of earmuff with NRR 48 dB.